The Effect of Coagulant Particle Size, Coagulant and Flocculant Dose on Remazol Yellow Dye Removal Effectiveness - Khalida Wijaya; Qonitah Fardiyah; Barlah Rumhayati (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Textile dye effluents are hazardous because many residual dyes are persistent, toxic, and potentially carcinogenic. This study assessed an environmentally friendly coagulation flocculation route to remove Remazol Yellow, an azo dye used in the batik industry in South Sulawesi, by substituting synthetic reagents with papaya (Carica papaya) seeds as a coagulant and Aloe vera gel as a flocculant. FTIR confirmed hydroxyl, carboxyl, and amine groups in papaya seeds, while Aloe vera gel was dominated by polysaccharide and carboxylate features. Jar tests were performed at room temperature using an initial dye concentration of 30 mg L−1. Coagulation was conducted for 5 min at 950 rpm, followed by flocculation for 30 min at 125 rpm and sedimentation for 30 min. Residual dye was measured by UV Vis spectrophotometry at 417 nm. Operational variables were optimized, including coagulant particle size (30 to 100 mesh), papaya seed dose (10 to 50 mg L−1), and Aloe vera gel dose (10 to 60 g L−1). The optimum particle size was 70 mesh, giving 60.4 percent removal. The optimum papaya seed dose was 20 mg L−1 with 83.5 percent removal, and the optimum Aloe vera gel dose was 50 g L−1, achieving 97.4 percent removal. These results demonstrate the potential of papaya seeds and Aloe vera gel as effective and sustainable materials for batik dye wastewater treatment.